COVID-19 pandemic as a socio-psychological influence on transformations in religion - Y. Gavrilova; E. Zakharova; M. Liga; M. Zhironkina; A. Barsukova (Acta Theologica)
This article aims to establish COVID-19’s sociopsychological influence on religion. This interdisciplinary study’s theoretical framework embraces the socialecological systems framework, the concept of deprivation, the theory of religious myth-making, religious individualism and bricolage, as well as the concept of quality of life. A sociological survey was conducted of 4,700 residents of Moscow and the Moscow region. The results revealed that the social sphere of society was relatively stable during the pandemic. Exploring COVID-19’s socio-psychological influence, this study examines transformations in religion that resulted from tactile deprivation.